Emotion Regulation In Early Childhood Within The Learning Context At Daarul Irsyad Kindergarten, Cianjur - Nova Tania Septiani; Eva Manfaatin Kartadinata; Ika Rustika Zainah (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Emotional regulation is an important aspect of early childhood education because it influences children’s self-control, social interaction, learning readiness, and self-confidence. Although previous studies have examined emotional regulation in young children, limited research has explored its relationship with self-confidence and the Identity Development (Jati Diri) element of the Merdeka Curriculum, particularly within the context of Islamic early childhood education. This study aimed to describe the process of emotional regulation among children aged five to six years in the learning context of Daarul Irsyad Kindergarten, Cianjur, identify the supporting and inhibiting factors, and analyze the teacher’s role in strengthening children’s self-confidence through emotional guidance. This study employed a qualitative descriptive approach using a case study method. Data were collected through observations, semi-structured interviews with the principal, teachers, and parents, as well as documentation of learning activities. The findings revealed that children’s emotional regulation developed through daily habituation, teacher guidance, positive reinforcement, peer interactions, religious practices, and family support. Children gradually learned to recognize and express their emotions appropriately, follow classroom rules, wait for their turns, resolve simple conflicts, and participate more confidently in learning activities. Teachers played a central role as guides, facilitators, motivators, and role models by creating a safe, warm, supportive, and values-based learning environment. The study concludes that emotional regulation contributes to the development of children’s self-confidence and supports the achievement of the Identity Development (Jati Diri) learning outcomes. The findings also highlight the importance of collaboration between schools and families in fostering children’s emotional competence, confidence, and character development within Islamic early childhood education settings.